Virtual Reality and Productivity in Knowledge Workers - Aufegger, Lisa; Elliott-Deflo, Natasha (Frontiers in Virtual Reality, 2022)
Productivity is an important factor of every organisation and has a significant impact on success and monetary wellbeing. Over the past few years, the substantial developments of digital technologies have encouraged a shift in the way we work and produce, from an office-based environment to “virtual work”. However, very little is known as to how virtual work and productivity can be supported by virtual reality (VR). We conducted two studies to extend previous productivity research in relation to VR: Study 1 examined the routes that connect the organisational context (i.e., knowledge workers) with the individual productivity position through the lens of remote working and distributed collaboration; Study 2 explored the nature of and connections between productivity in individuals and teams working in VR. Based on the findings we demonstrate how the future of VR could enact in knowledge workers’ daily productivity, by developing a VR productivity framework that represents physical, environmental, cognitive, and behavioural needs to ensure productivity and organisational growth. Theoretical and practical implications of the findings are discussed.